2017
DOI: 10.1364/ol.42.004800
|View full text |Cite
|
Sign up to set email alerts
|

Scaled model guidelines for solar coronagraphs’ external occulters with an optimized shape

Abstract: One of the major challenges faced by externally occulted solar coronagraphs is the suppression of the light diffracted by the occulter edge. It is a contribution to the stray light that overwhelms the coronal signal on the focal plane and must be reduced by modifying the geometrical shape of the occulter. There is a rich literature, mostly experimental, on the appropriate choice of the most suitable shape. The problem arises when huge coronagraphs, such as those in formation flight, shall be tested in a labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…6. To take into account the effects of the full 3D structure, a small-scale model could be realized and its Fresnel diffraction studied in a montage that conserves the optical etendue, as described by Landini et al (2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6. To take into account the effects of the full 3D structure, a small-scale model could be realized and its Fresnel diffraction studied in a montage that conserves the optical etendue, as described by Landini et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…In this section we seek to derive an optimal envelope for an ensemble of disks. To this aim, we follow the approach of Landini et al (2017), which is to replace the 3D structure by a series of 2D cuts. We assume that this remains valid within the approach of Fourier optics, an assumption that would require further investigation.…”
Section: The Optimal Envelope For Multiple Disksmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus Landini et al (2010) and Landini et al (2011) compared the efficiency of linear segments of various occulters, and thick occulters were again found to be more efficient, with the advantage being about factor of two. Later, Landini et al (2016Landini et al ( , 2017a developed an analytical model and showed how an ASPIICS-size configuration can be rescaled to a laboratory size (linear scaling for distances, and quadratic scaling for thicknesses) so that the experiments would be representative. However, in this case, the intensity of the diffracted light can be measured only in the entrance aperture plane and not in the detector plane, as otherwise the remaining optical system would be scaled down to an unrealistic size.…”
Section: Discussionmentioning
confidence: 99%
“…In the entrance aperture plane the intensity of the diffracted light enhances very slightly in the umbra region with the radial distance from the axis; see Fig. 4 in Landini et al (2017a), Fig. 5 in RR17, and Fig.…”
Section: Scattered Lightmentioning
confidence: 98%